Protocol for efficient generation and characterization of adeno-associated viral vectors - Jungmann, Andreas; Leuchs, Barbara; Rommelaere, Jean; Katus, Hugo; Müller, Oliver J. (Human gene therapy. Methods, 2017)
Adeno-associated virus vectors are a powerful tool for gene transfer approaches. We have established a simple and fast plasmid-based production system for achieving high adeno-associated virus titers within 6 working days. The same procedure can be used for all serotypes and thus allows direct comparability of different serotypes. In this protocol we describe a step-by-step procedure that results in well-characterized vectors suitable for both in vitro approaches and preclinical studies.
Gesehen am 10.08.2018
Published Online:1 October 2017